The fair maid of Perth - Scott, Walter, 1771-1832 (Scott, Walter, 1771-1832. Waverley novels (Edinburgh ed.), 1999)
Find Out What Scott Really WroteGoing back to the original manuscripts, a team of scholars has uncovered what Scott originally wrote and intended his public to read before errors, misreadings and expurgations crept in during production.The Edinburgh Edition offers you:A clean, corrected textTextual historiesExplanatory notesVerbal changes from the first-edition textFull glossariesTitle DescriptionThe Fair Maid of Perth centres on the merchant classes of Perth in the fourteenth century, and their commitment to the pacific values of trade, in a bloody and brutal era in which no right to life is recognised, in which the Scottish nobles fight for control of the weak Scottish monarchy, and clans are prepared to extinguish each other to gain supremacy in the central Highlands. It is a remarkable novel, in part because late in his career Scott has a new subject, and in part because he employs a spare narrative style that is without parallel in the rest of his oeuvre. Far too many critics, from his son-in-law J.G. Lockhart to the present day, have written off late Scott, and seen his last works as evidence of failing powers. Readers of the Edinburgh Edition of The Fair Maid of Perth will see that these critics are mistaken, for in it we witness a luminous creative intelligence working at high pressure to produce a tightly organised and deeply moving novel.